Three Decades of Progress and Commitment: Brief Historical Landmarks of ‘Galician Medical Journal’ Journey - Oksana Popadynets; Taras Kotyk; Oksana Fedoruk; Nadiya Tokaruk; Viktoria Bedei (Galician Medical Journal, 2023)
The 'Galician Medical Journal' celebrates its thirtieth anniversary, marking three decades of impactful contributions to the medical field. Since its establishment in 1994, the journal has evolved, overcoming challenges to become a significant platform for disseminating medical knowledge. In this editorial, we briefly reflect on the historical evolution of the journal, highlighting its transformation from local origins to an active involvement in the global medical community.